Understanding the factors that impact effective uptake and maintenance of HIV care programs in South African primary health care clinics - Alastair van Heerden; Xolani Ntinga; Sheri A. Lippman; Hannah H. Leslie; Wayne T. Steward (Archives of Public Health, 2022)
Abstract Background There is an increasingly urgent gap in knowledge regarding the translation of effective HIV prevention and care programming into scaled clinical policy and practice. Challenges limiting the translation of efficacious programming into national policy include the paucity of proven efficacious programs that are reasonable for clinics to implement and the difficulty in moving a successful program from research trial to scaled programming. This study aims to bridge the divide between science and practice by exploring health care providers’ views on what is needed to implement new HIV programs within existing HIV care. Methods We conducted 20 in-depth interviews with clinic managers and clinic program implementing staff and five key informant interviews with district health managers overseeing programming in the uMgungundlovu District of KwaZulu-Natal Province, South Africa. Qualitative data were analyzed using a template approach. A priori themes were used to construct templates of relevance, including current care context for HIV and past predictors of successful implementation. Data were coded and analyzed by these templates. Results Heath care providers identified three main factors that impact the integration of HIV programming into general clinical care: perceived benefits, resource availability, and clear communication. The perceived benefits of HIV programs hinged on the social validation of the program by early adopters. Wide program availability and improved convenience for providers and patients increased perceived benefit. Limited staffing capacity and a shortage of space were noted as resource constraints. Programs that specifically tackled these constraints through clinic decongestion were reported as being the most successful. Clear communication with all entities involved in clinic-based programs, some of which include external partners, was noted as central to maximizing program function and provider uptake. Conclusions Amid the COVID-19 pandemic, new programs are continuously being developed for implementation at the primary health care level. A better understanding of the factors that facilitate and prevent programmatic success will improve public health outcomes. Implementation is likely to be most successful when programs capitalize on endorsements from early adopters, tackle resource constraints, and foster greater communication among partners responsible for implementation.